Compact hairpin line bandpass filter with improved spurious passbands suppression. Issue 8 (3rd August 2021) - Das, Tarun Kumar; Chatterjee, Sayan
ABSTRACT: The present paper describes the design of a folded hairpin-line bandpass filter centred at 2.5 GHz applicable for Wireless Local Area Network (WLAN) with improved spurious suppression. The size of the conventional filter has been reduced by 30% by folding the open-end arms towards the inward direction. Thus, improvements over the skirt characteristics and shifting of the second harmonic to higher frequency region have been obtained. However, the attenuation level at the harmonic frequency remains almost unaffected. Subsequently, the inner and outer edges of the coupled-lines have been modified with Minkowski fractals to compensate for the modal phase velocities. As a result, more than 36 dB of harmonic suppression up to three times the centre frequency along with size reduction of 30% has been achieved.